2019
DOI: 10.1590/0100-5405/187782
|View full text |Cite
|
Sign up to set email alerts
|

Damage caused by Meloidogyne javanica and Pratylenchus zeae to sugarcane cultivars

Abstract: Nematodes are important parasites of sugarcane, significantly reducing the yield and the longevity of the crop. Damage caused by them varies with the susceptibility of sugarcane cultivars; thus, it is important for growers to learn the reaction of new genotypes in order to better direct control measures. The objective of this study was to evaluate the damage caused by nematodes to cultivars newly released for commercial planting. Two experiments were conducted in fields infested by Meloidogyne javanica and Pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…In the experiment 3, although the population of P. zeae decreased in the plots treated with carbosulfan at least until four months after planting, there were no differences between the treatments regarding yield. This occurred because RB867515, the variety planted in the experiment 3, is tolerant to P. zeae (Dinardo-Miranda et al 2019) were observed in plots treated with carbosulfan, the highest yields were also observed for this treatment, differing significantly from the control. In these two experiments, the yield in treatments with B. subtilis + B. licheniformis did not differ from the control or the treatment with carbosulfan.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In the experiment 3, although the population of P. zeae decreased in the plots treated with carbosulfan at least until four months after planting, there were no differences between the treatments regarding yield. This occurred because RB867515, the variety planted in the experiment 3, is tolerant to P. zeae (Dinardo-Miranda et al 2019) were observed in plots treated with carbosulfan, the highest yields were also observed for this treatment, differing significantly from the control. In these two experiments, the yield in treatments with B. subtilis + B. licheniformis did not differ from the control or the treatment with carbosulfan.…”
Section: Resultsmentioning
confidence: 93%
“…The most used nematicides in sugarcane are the chemical ones, which rapidly reduce nematode populations and protect the growing plant from damage. Although these products maintain a low population of nematodes for only a few months after application, they contribute to significant increases in yield in infested areas, when compared to untreated areas (Dinardo-Miranda & Mengatti 2004, Dinardo-Miranda et al 2008, Dinardo-Miranda et al 2010, Silva et al 2006). However, since chemical nematicides in the soil are associated with environmental impacts, researches with biocontrol agents have acquired a greater importance.…”
Section: Controle Biológico De Nematoides Fitoparasitos Em Canaviaismentioning
confidence: 99%
“…Both compounds were previously tested in different varieties of sugarcane and an increment of 10% and 5% was also observed. The authors explained these differences by measuring levels of nematode infestation, which indicate the efficiency of pesticides applied in the studies [39,40]. Carbamates penetrate into the phytoparasite nematode and induce changes in metabolism leading them to death [41].…”
Section: Discussionmentioning
confidence: 99%
“…In sugarcane fields, rhizosphere conditions define root development, which is affected by plant-microbial interactions, nutrient and water availabilities (Darrah 1993), soil characteristics, root exudates and root decomposition (Singh et al 2013), andsoil pests (Dinardo-Miranda andFracasso 2010;Dinardo-Miranda et al 2019). Although all factors above may affect sugarcane regrowth, here the role of root system size as a source of reserves was addressed and there is no reason for assuming that this dependency is not present in field-grown plants.…”
Section: Discussionmentioning
confidence: 99%